The case study: Shyness in adolescence - Readi Varillas, Rosa Yalile (2021)
The research presented below is a clinical case of a 16-year-old adolescent who displays shy behavior, lacking social skills, Attention Deficit Disorder, and family problems. This study aims to identify the factors that influence the development of shy behavior, as well as social skills; through psychological tests, personal and family history, and interviews completed to the examinee, which has been possible to argue about the various factors that have influenced and are still perceived in respect of the shy behavior and social skills deficit found in the examinee. Once the comprehensive assessment was conducted, a therapeutic process based on cognitive behavioral therapy began, focused on the recognition of emotions, identification of thoughts, differentiation in the recognition between thought, emotion and behavior, cognitive restructuring, symbolic modeling and relaxation training.